Circadian Levels of Serum Melatonin and Cortisol in relation to Changes in Mood, Sleep, and Neurocognitive Performance, Spanning a Year of Residence in Antarctica. (13th December 2012) - Premkumar, Madhumita; Sable, Tarulata; Dhanwal, Dinesh; Dewan, Richa
Abstract : Background . Altered circadian cortisol and melatonin rhythms in healthy subjects exposed to an extreme polar photoperiod results in changes in mood and sleep, which can influence cognitive performance. Materials and Methods . We assessed the circadian rhythm of 20 subjects who wintered over at Maitri (70 ° S, 11 ° E), India's permanent Antarctic station, from November 2010 to December 2011. Serum cortisol and melatonin levels were measured by radioimmunoassay at 8 am, 3 pm, 8 pm, and 2 am in a single day, once each during the polar summer and winter photoperiods. Conventional psychological tests, Depression, Anxiety, and Stress Scale (DASS-42), Epworth Sleepiness Scale (ESS), and a computerized neurocognitive test battery were used to measure mood, sleep, and cognitive performance. Results . The mean scores for DASS42 were higher during midwinter suggesting the presence of "overwintering." Mean diurnal cortisol levels during summer and winter were comparable, but the levels of melatonin were markedly higher during winter. Higher 8 am melatonin levels were associated with better sleep quality, lower depression scores, and better performance in tasks like attention, visual memory, and arithmetic. Conclusion . Timing of artificial light exposure and usage of melatonin supplements in improving sleep and cognitive performance in expedition teams are of future research interest.